LESSON STUDY AS A PLATFORM FOR ENGAGING SPEAKINGLECTURERS IN DOING TEACHER PROFESSIONAL DEVELOPMENT - Luthfiyyah, Roghibatul (Perspective Jurnal Pendidikan Bahasa Inggris, 2015)
Abstract This case study aims at investigating the implementation of Lesson Study at English Education Department of a private university in Indonesia. Particularly, it reveals the activities of lesson study and teachers prolonged engagement in reflection activities. This studyprovides worthwhile chance for teachers to create a learning community in which they can develop their knowledge as professionals. There were four speaking lecturers, one lecturer as a model and others as participants, who worked collaboratively to formulate learning goals, lesson plan, classroom observation, teaching learning reflection, revision of the lesson for improvement, and re-teaching the revised lesson. The data were collected from the classroom observation, interview, community discussions, and reflection in two cycles. The findings reveal that the activities of Lesson Study facilitate the lecturers in designing proper teaching objectives and materials. Furthermore, it also can be regarded as a platform for teachers to have a learning community in which they can share and develop their teaching qualification. Keywords: Lesson Study, Teachers Professional Development, Prolonged Engagement